Aviation and International Cooperation: Human and Public Policy Issues - Abeyratne, Ruwantissa (Springer, 2016)
This book addresses an essential gap in the regulatory regime, which provides legislation, statements and guidelines on airlines, airports, air navigation services providers and States in the field of aviation, but is notably lacking when it comes to the rights of the airline passenger, and the average citizen who is threatened by military air strikes. It addresses subjects such as international resolutions on human rights and other human rights conventions related to aviation that impact both air transport consumers and people on the ground who are threatened by air strikes through drone attacks; disabled and obese airline passengers; compensation for delayed carriage and the denial of carriage; noise and air pollution caused by aviation and their effects on human health and wellbeing; prevention of death or injury to passengers and attendant compensatory rights; risk management; relief flights; and racial profiling. These subjects are addressed against the backdrop of real case studies that include but are not limited to instances of drone attacks, and contentious flights in the year 2014 such as MH 370, MH 17 and QZ 8501.